O ADOECER DE CÂNCER: A PERCEPÇÃO DE PACIENTES EM TRATAMENTO QUIMIOTERÁPICO AMBULATORIAL - Christo, Zuriel Tais Mello de (2021)
Introduction: In recent decades, cancer is one of the diseases that have most affected people; it is prevalent and multifaceted. It does not choose age, sex, ethnicity or religion, and appears in the most varied ways. What is still questioned and debated are the causes and the perception that patients attribute to their illness in certain stages of this disease. Given this scenario, it is relevant to understand and reframe the relationship that men have with health and illness, the importance of psycho-oncology in the context of cancer, the perception that patients attribute to the origin of the disease during psycho-oncology, and the improvement of mental health through psychological support in the emerging context of cancer. Objective: Understand the perception of falling ill in patients going through chemotherapy treatment for lung, pancreas, rectum, and brain cancers. Methodology: A qualitative approach with an exploratory and descriptive character was used. The data were obtained from recorded semi-structured interviews that were transcribed and analyzed to understand the perception of cancer patients undergoing ambulatory chemotherapy treatment regarding falling ill with the disease. Results: In the analyses, it was possible to comprehend that the patients’ perception derives from the resumption of their life stories, the analysis of their habits, the genetic recognition, the strengthening of the affections, the absences and excesses done and/or suffered until the day of the diagnosis. Moreover, this perception is continuously made and remade throughout the trajectory of falling ill because, for some subjects, the perception is only elaborated from cancer experiences. Conclusion: In the compilation, it was possible to conclude that the patients’ perception is far beyond physical involvement; it is configured and elaborated throughout the trajectory of the disease and the resumption of the life story of each subject, making it possible for the patient to attribute meaning or not to their illness, despite certainly providing better living of the phases of their life cycle.